The First to be Destroyed The Jewish Community of Kleczew and the Beginning of the Final Solution - Glowacka-Penczynska, A. (Academic Studies Press, 2015)
The Jewish community of the city of Kleczew came into existence in the sixteenth century. It remained large and strong throughout the next four hundred years, and in the eighteenth and nineteenth centuries it constituted 40-60% of the total population. The German army entered Kleczew on September 15, 1939, shortly after the outbreak of World War II. The communities of Kleczew and the vicinity were among the first Jewish collectives in Europe to be totally destroyed. The events presented in this book reveal that the organization of deportations and the methods of mass murder conducted in this district, by Kommando Lange, served as a model that would be applied later in the death camps during the mass extermination of Polish and European Jewry. If so, it was in the woods near Kleczew that the "Final Solution of the Jewish Question" began.